La dislexia y sus efectos en la educación virtual, en los estudiantes de cuarto año egb del paralelo “a”, de la Escuela de Educación Básica “Luis Aurelio González” del cantón Guaranda, provincia Bolívar, periodo 2021-2022 - Zapata Mazabanda, Andrea Lizbeth (2022)
Dyslexia and its effects in virtuality education in fourth graders is a problem that affects their entire learning process, since it does not allow them to have a comprehensive reading and means that all the effort made by the student remains in the classroom. nothing. This research work is identified with the theme: dyslexia and its incidence in virtual education, in fourth year EGB students of parallel "a", of the "Luis Aurelio González" basic education school of the Guaranda canton, Bolívar province., period 2021-2022, which highlights the great importance for the development of their learning, here is the commitment of their teachers to work with a group of boys who suffer from these problems. The activities that are developed in this research are based on a whole process that allowed knowing a whole problem through the application of tests and interviews with the responsible educator, in order to have a clear vision of the problem and propose change strategies for the benefit of students with dyslexia. This research work is developed in three parts: The theoretical framework, the same one that helps as a scientific support to all this problem as far as dyslexia is concerned, because it is proven that a child with dyslexia cannot develop their knowledge in a normal way like the rest of their classmates. Then we have the methods and techniques of the investigation, the instruments and the analyzes and results and their representation in charts and graphs. And finally we have the proposal, which seeks to provide a solution to this problem found in children with dyslexia, is based on the application of crossword puzzles, which will help to improve reading comprehension in large parts, since with the tests carried out an interest in working has been seen and they do it slowly but with great effort.